Analysis of Resonance Characteristics of Multi-storey Buildings Based on Microtremor Measurements - Muhammad Derrio; Soe Pandi; Aser Eben Ezer Sihombing; Joy Adithia Tarigan; Fardin Hasibuan (METALOGRAM, 2025)
The diverse functions of buildings today require designs that minimize potential damage, particularly from natural disasters. Earthquakes are one of the natural disasters that pose a significant threat to buildings. For example, the earthquake that occurred in Yogyakarta in 2023 caused damage to various building facilities. This study aims to identify the vulnerability level of buildings using microtremor data to obtain the natural frequency value of the building (fb), building resonance index (R), and building vulnerability index (Kb). This research has been carried out in multi-storey buildings by measuring natural frequencies on the building and its basic land. The recorded vibration data were analyzed with the H / V technique to get its natural frequency value. The measurement results of building floor vibrations using the GPL-6A3P accelerometer show that the natural frequency